Empresarios y familias en el negocio del oro en Chile, 1730-1785 - Jaime J. Lacueva Muñoz (Centre de Recherches sur les Mondes Américains, 2015)
This work aims to present a hierarchy of entrepreneurs involved in the mining business through tax declaration and gold coinage records in Santiago Royal Treasury and Mint. Starting from the literature which focus the Chilean elite mainly on titles and entails, a wider concept of the mercantile elite is proposed, based more on turnover than on belonging to nobility. Finally, it concerned to the continuity of family business groups formed by strategic marriage alliances within the same business sector, both merchants mermbers of the so-called aristocratic group and other entrepreneurs lacking of such status, but also important for their economic performance.